Advances in thermoplastic polyurethane composites reinforced with carbon nanotubes and carbon nanofibers: A review. (April 2015) - Sattar, Rabia; Kausar, Ayesha; Siddiq, Muhammad
Carbon nanotubes (CNTs) have long been recognized as the stiffest and strongest man-made material known to date. Owing to high electrical conductivity, CNTs have also gained interest in the area of electrical appliances and communication related applications. Moreover, carbon nanofibers (CNFs) depict fine electrical and mechanical profile. Due to their miniscule size, excellent mechanical, electrical, and thermal properties, CNTs can only be beneficial if they are homogeneously dispersed and embedded into light-weight engineering polymer matrices. Adding small amounts of CNTs strongly improve the electrical, thermal, and mechanical properties of the composites. In order to enhance their chemical affinity to polymer matrices, chemically modifying the graphitic sidewalls and tips is necessary. This article reviews the processing technology and improvement of various properties of carbon nanotube-reinforced thermoplastic polyurethane (PU) composites. Initially, the structure, morphology, mechanical, thermal, and electrical properties of nanotubes are described. Then various strategies for fabricating PU/CNTs composites and their properties are discussed. To conclude, recent developments in the field of mechanical, thermal, and electrical properties of thermoplastic PU reinforced with nanotubes and nanofibers are reviewed. A brief account regarding the toxicity and environmental safety aspects of carbon nanomaterials is also included in this article.